Heat transfer analysis of an integrated double skin façade and phase change material blind system - Li, Yilin; Darkwa, Jo; Kokogiannakis, Georgios (Elsevier, 2017)
In this study, the heat transfer in an integrated double skin facade (DSF) and phase change material (PCM) blind system has been theoretically analysed. Both heat transfer and airflow models with CFD methods have been developed for the integrated DSF and PCM blind system. Data from an existing typical DSF building have been obtained in order to define input parameters for the simulation exercise and validate the numerical models. The temperature and velocity fields in DSF with the PCM blind system has been predicted under overheating scenario using the ANSYS Workbench FLUENT software and been compared with case of conventional aluminium blind system. This study has shown that the integrated PCM blind system was able to reduce the average air temperature and outlet temperature of the DSF while improving the convective heat transfer between the cavity air and the blades. Compared with the aluminium blind, the PCM blind can absorb large amount of excessive heat in the cavity. Overall the integrated PCM blind system has the potential to be used as an effective thermal management device for minimising the overheating effect in DSFs.